Energy cost of badminton footwork: A novel experimental approach - Pugliese, L.; Pavei, G.; La Torre, A.; Gianfelici, A.; Rampichini, S.; Esposito, F. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Despite the increasing body of literature on badminton, no data exist concerning the energy cost of badminton movement, known as "footwork." This study introduces a novel experimental approach to assessing the energy cost of footwork by applying established metabolic measurement techniques to badminton-specific movement patterns for the first time. In addition, it aims to verify whether differences exist between 2 different movement combinations.